IMPLEMENTASI ICE BREAKING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS I DI SEKOLAH DASAR SUBSIDI TARBIYATUL ISLAM SAMBAS TAHUN PELAJARAN 2023-2024 - Patimah Patimah; Topik, Sera Yuliantini (ADISAM PUBLISHER, 2024)
This research was conducted because there were problems among some of the class I students at subsidized elementary schools Tarbiyatul Islam Sambas is less enthusiastic when learning, there are students who are sleepy and there are also students who look passive and pay little attention to the teacher when explainin the lesson material, this is because students prefer to be in their own world such as drawing, talking and playing with his des mates, joking and making noise, these problems indicate weakness student’s motivation to study. Therefore, the class I teacher tries to create a pleasant class atmosphere by using the ice breaker game. The aim of this research is to reveal the types, impact and supporting and inhibiting factors carried out by class I teachers in using ice breaking. This research uses a qualitative approach with a descriptive type. The results of the research are the type of ice breaking waht wase done was ice breaking, applause, shouts, songs, body movements and games. Impact of implementation ice breaking students are happy when the ice breaking is done, students are enthusiastic and more active in learning. Supporting and inhibiting factors for implementing ice breaking, supporting factors for students being happy when ice breaking is carried out, students become enthusiastic and more active in learning, the inhibiting factors are: different student characteristics and time constraints.